2008
DOI: 10.1016/j.tvjl.2007.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Uterine diseases in cattle after parturition

Abstract: Bacterial contamination of the uterine lumen is common in cattle after parturition, often leading to infection and uterine disease. Clinical disease can be diagnosed and scored by examination of the vaginal mucus, which reflects the presence of pathogenic bacteria such as Escherichia coli and Arcanobacterium pyogenes. Viruses may also cause uterine disease and bovine herpesvirus 4 (BoHV-4) is tropic for endometrial cells, causing a rapid cytopathic effect. The elimination of pathogens by the innate immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
285
4
42

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(346 citation statements)
references
References 55 publications
15
285
4
42
Order By: Relevance
“…The impact of negative energy balance on reproductive performance in dairy cows is well established (Beam and Butler, 1998). In agreement with the present study, stage of lactation has previously been shown to be associated with resumption of the ovarian cyclicity in both dairy (Rhodes et al, 2003;Gautam et al, 2010) and beef cows (Murphy et al, 1990) as well as the occurrence of cystic structures in dairy cows (Gröhn et al, 1994) and the uterine health of cows (Sheldon et al, 2008). As lactation progresses, energy balance improves (Berry et al, 2006), leading to more energy available for reproductive function and other bodily functions.…”
Section: Paritysupporting
confidence: 91%
See 2 more Smart Citations
“…The impact of negative energy balance on reproductive performance in dairy cows is well established (Beam and Butler, 1998). In agreement with the present study, stage of lactation has previously been shown to be associated with resumption of the ovarian cyclicity in both dairy (Rhodes et al, 2003;Gautam et al, 2010) and beef cows (Murphy et al, 1990) as well as the occurrence of cystic structures in dairy cows (Gröhn et al, 1994) and the uterine health of cows (Sheldon et al, 2008). As lactation progresses, energy balance improves (Berry et al, 2006), leading to more energy available for reproductive function and other bodily functions.…”
Section: Paritysupporting
confidence: 91%
“…The clearance of pathogens from the uterus postpartum can take up to 35 days (Sheldon and Dobson, 2004), while normal involution of the uterus can take up to 40 days (Sheldon et al, 2008). In the present study, uterine score improved (indicating uterine tone had improved and the quantity of fluid present in the uterus had reduced) with stage post-calving and this may simply be a result of the natural process of the uterine involution postpartum.…”
Section: Paritysupporting
confidence: 44%
See 1 more Smart Citation
“…Para que os animais voltem a conceber após a parição é preciso que ocorram alguns eventos no pós-parto imediato como a eliminação da placenta, involução uterina, regeneração do endométrio, eliminação bacteriana e retorno ovariano à ciclicidade (Sheldon 2004, Sheldon et al 2008. Dessa forma, para lograr bons índices sanitários e reprodutivos do rebanho, é importante conhecer o padrão fisiológi-co do metabolismo da raça em questão, para assim, poder diagnosticar precocemente eventuais desordens e intervir de maneira a saná-las.…”
Section: Introductionunclassified
“…Investigators have reported differing findings about the percentage of neutrophils that indicates subclinical endometritis in cows. Hammon et al (2006) established as subclinical endometritis-positive those cows with counts of PMN > 25% performed at 28 ± 3 days postpartum, while others established percentages higher than 18% or 10% in endometrial samples collected between days 21 to 33 or 34 to 47 after calving, respectively (Kasimanickam et al 2004;Sheldon et al 2006). On the other hand, it has been reported that more than 5% of PMNs is a significant cut-off point for the endometrial inflammatory response in cows sampled using uterine lavage between 40 and 60 days postpartum (Drillich et al 2005;Gilbert et al 2005).…”
mentioning
confidence: 99%